2020
DOI: 10.1049/iet-rpg.2019.0614
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term wind power forecasting based on two‐stage attention mechanism

Abstract: Wind power is usually closely related to the meteorological information around the wind farm, which leads to the fluctuation of wind power and makes it difficult to predict precisely. In this study, a wind power forecasting model based on longshort-term memory network two-stage attention mechanism is established. The attention mechanism is extensively employed to weigh the input feature and strengthen the trend characteristic of wind power. The intermittency and volatility feature of the wind are efficiently m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In summary, the main contributions of this approach are I) Despite the fact that there is numerous research on short-time, medium-time, and long-time wind power prediction [19][20][21][22][23][24][25][26][27][35][36], the only study related to the extremely short-time prediction was presented in [7]. The present study proposing a more efficient prediction method compared to [7].…”
Section: Time Horizon Range Referencesmentioning
confidence: 94%
See 1 more Smart Citation
“…In summary, the main contributions of this approach are I) Despite the fact that there is numerous research on short-time, medium-time, and long-time wind power prediction [19][20][21][22][23][24][25][26][27][35][36], the only study related to the extremely short-time prediction was presented in [7]. The present study proposing a more efficient prediction method compared to [7].…”
Section: Time Horizon Range Referencesmentioning
confidence: 94%
“…Extremely short-time ∆ ≤ 0.02 Only [7] and [9] Very short-time [27] In the other hand, based on time periods, wind speed/power forecasting methods are classified in Table I to five categories; extremely short-time, very short-time [19], [20], short-time [21]- [23], medium-time [24], [25] and long-time forecasting [26], [27]. The first group of this division is long-time forecasting methods, which usually include forecasting from 1 day to 1 week.…”
Section: Time Horizon Range Referencesmentioning
confidence: 99%
“…Results show that AM can effectively improve the accuracy of load forecasting [26]. Li et al established a wind power forecasting model based on LSTM network two-stage attention mechanism and found that the attention mechanism is extensively employed to weight the input feature and strengthen the trend characteristic [27]. Wang et al proposed a novel short-term load forecasting method based on attention mechanism, rolling update, and bidirectional long short-term memory neural network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Forecasting and modelling the time variations of wind farm quantities such as wind speed or wind power is always a hot topic and many studies recently were published in this regard [20][21][22][23][24][25][26]. However none of them were about the extremely short time forecasting or modelling this kind of variations.…”
Section: Introductionmentioning
confidence: 99%